Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2478/fon-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression symptoms among ovarian cancer patients in China: a cross-sectional study

Abstract: ObjectiveTo investigate the prevalence of cancer-related depression and anxiety in western China among patients with ovarian cancer and analyze their influencing factors.MethodsIn this prospective cross-sectional study, qualified patients were asked to fill in questionnaires. Multivariate analysis and binary logistic regression analysis were used to test the associations among symptoms of depression and anxiety, coping styles, and influencing factors.ResultsA total of 270 ovarian cancer inpatients who met the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…As a result of searching electronic databases, 1371 articles were obtained, of which 1221 remained after removing duplicates. In the next step, after screening based on the title, abstract, and full text based on the inclusion and exclusion criteria, 18 studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were selected for meta-analysis (Fig. 1), of which 17 studies [13][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30] reported the prevalence of depression and 16 studies [13][14][15][16][17][18][19][22][23][24][25][26][27][28]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result of searching electronic databases, 1371 articles were obtained, of which 1221 remained after removing duplicates. In the next step, after screening based on the title, abstract, and full text based on the inclusion and exclusion criteria, 18 studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were selected for meta-analysis (Fig. 1), of which 17 studies [13][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30] reported the prevalence of depression and 16 studies [13][14][15][16][17][18][19][22][23][24][25][26][27][28]…”
Section: Resultsmentioning
confidence: 99%
“…1), of which 17 studies [13][14][15][16][17][18][20][21][22][23][24][25][26][27][28][29][30] reported the prevalence of depression and 16 studies [13][14][15][16][17][18][19][22][23][24][25][26][27][28][29][30] reported the prevalence of anxiety in women with ovarian cancer. Of 18 included studies, 6 were conducted in Australia [13,15,20,25,26,30], 2 in the USA [16,17], 2 in the United Kingdom [18,19], 2 in China [22,23], and one in each of the following countries: Norway [14], Czech Republic [21], Thailand [24], the Netherlands [27], Italia [28], and Poland…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations